2011
DOI: 10.1021/jf104632a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hesperetin against Oxidative Stress via ER- and TrkA-Mediated Actions in PC12 Cells

Abstract: Hesperetin is known to activate estrogen receptors (ERs). Estrogen-mediated neuroprotection could be via both ER and tyrosine kinase receptor (Trk) signaling. This study tested whether hesperetin protected PC12 cells from hydrogen peroxide induced oxidative damage via ER- and/or TrkA-mediated actions. Hesperetin (0.1, 1, and 50 μM) inhibited cell viability decreases and reactive oxygen species, intracellular calcium level, and caspase-3 activity increases in H(2)O(2)-induced PC12 cells. Such actions were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…hours. Then, the whole-cell proteins were extracted using RIPA buffer (50 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1% Triton X-100, 0.5% sodium deoxycholate, 1 mM ethylenediaminetetraacetic acid (EDTA), 0.1% sodium azide, 50 mM NaF, and 0.1% sodium dodecyl sulfate (SDS), and 1 mM phenylmethanesulfonyl fluoride (PMSF) (26). Protein concentrations were determined in supernatant by Nanodrop-2000 Spectrophotometer.…”
Section: Real-time Quantitative Polymerase Chain Reaction For Il-6mentioning
confidence: 99%
See 1 more Smart Citation
“…hours. Then, the whole-cell proteins were extracted using RIPA buffer (50 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1% Triton X-100, 0.5% sodium deoxycholate, 1 mM ethylenediaminetetraacetic acid (EDTA), 0.1% sodium azide, 50 mM NaF, and 0.1% sodium dodecyl sulfate (SDS), and 1 mM phenylmethanesulfonyl fluoride (PMSF) (26). Protein concentrations were determined in supernatant by Nanodrop-2000 Spectrophotometer.…”
Section: Real-time Quantitative Polymerase Chain Reaction For Il-6mentioning
confidence: 99%
“…The gels were transferred and blotted onto polyvinylidene difluoride membranes (PVDF). Then, the membranes were placed into a blocking buffer containing 5% skim milk powder in TBSTween buffer (10 mM Tris, 100 mM NaCl, 0.1 mM Tween-20), and pH 7.4 for overnight at 4°C (26). The membranes were rinsed 3 times in TBS-Tween buffer for 10 minutes and subjected to primary antibodies against phosphorylated STAT3, phosphorylated p44/42 ERK1/2, and phosphorylated AKT at room temperature for 3 hours.…”
Section: Western Blottingmentioning
confidence: 99%
“…Then, cells were harvested and subsequently were lysed in icecold RIPA buffer (50 mM Tris-HCl with pH 8, 150 mM NaCl, 1% Triton 100X, 0.5% sodium deoxycholate, 1 mM EDTA, and 0.1% sodium azide) (17). Lysates were incubated at 4°C for 30 minutes and were centrifuged for 10 minutes at 12000 RPM.…”
Section: Western Blottingmentioning
confidence: 99%
“…Then, denatured proteins were separated by 10% SDS-polyacrylamide gel electrophoresis and pre-stained blue protein markers (BioRad) were used for molecular-weight determination. Separated proteins were transferred into polyvinylidene difluoride membranes and were placed in blocking solution (2.5% w/v skim milk powder in Tris-buffered saline (TBST) with 0.1% Tween-20) for overnight at 4°C (17). Then, the membranes were washed 3 times in TBS-Tween buffer for 10 minutes.…”
Section: Western Blottingmentioning
confidence: 99%
“…In addition, Kawaguchi et al (2004) showed that pre-treatment with hesperetin could suppress infectioninduced endotoxin shock in mice and a significant reduction of bacterial numbers during infection due to the activation of host defence mechanisms. Furthermore, it protects rat neurons cells against various types of insults associated with many neurodegenerative diseases (Hwang and Yen, 2011). Results indicate that hesperetin glucuronides protects against UV-A radiationinduced necrotic cell death (Tvrrell and Rice-Evans, 2003) and treats symptoms of radiation sickness (Saad, 2005).…”
mentioning
confidence: 99%